Organizational Da'wah and Police Character Formation: A Da’wah Sociology Perspective - Mevyeka Nurhalizah; Aufa Aurigza Haq; Faiz Miftahul Huda (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze the forms and patterns of organizational da’wah implemented through internal communication in shaping the character of police personnel, as well as the process of internalizing da’wah values within structural and cultural contexts. The research adopts a qualitative approach grounded in the sociology of da’wah, utilizing Structural Da’wah Theory as the primary analytical framework. Data were collected through in-depth interviews with police personnel, observations of internal communication practices, and an analysis of institutional documents related to character development and organizational values. The findings reveal that organizational da’wah within the police institution operates through structural mechanisms embedded in the command system, regulatory frameworks, and organizational culture, positioning internal communication as a key medium for the internalization of values such as discipline, integrity, responsibility, and public service. The internalization process is facilitated through leadership exemplarity, habituation within institutional routines, and the reinforcement of norms through recurring organizational symbols and practices. Both structural dynamics, including policy consistency and leadership legitimacy, and cultural dynamics, such as individual resistance and diverse value backgrounds, influence the character formation process. This study emphasizes the strategic role of structural da’wah mediated by internal communication in fostering the character of police personnel, which is highly dependent on the alignment between formal organizational structures and internal organizational culture.